The flavonoid-sensing regulator AefR is involved in modulating quorum sensing through repressing the MexEF-OprN efflux pump in Pseudomonas fluorescens - Yu Xiao-Quan; Han Jian-Ting; Feng Han-Zhong; Hou Jun; Wang Zhi-Ping; Yong-Xing He (mSystems)
ABSTRACT Flavonoids, a major component of plant root exudates, play a crucial role in mediating plant-microbe interactions. However, the mechanisms by which flavonoids are perceived and trigger downstream signaling events in microbes remain largely unknown. In this study, we characterized AefR, a flavonoid-sensing transcriptional regulator from Pseudomonas fluorescens 2P24, a plant growth-promoting rhizobacterium (PGPR) known for its biocontrol properties. AefR was found to repress the expression of the mexEF-oprN efflux pump, which putatively exports N-acylhomoserine lactones (AHLs). This repression attenuates the PcoR/PcoI quorum-sensing system, leading to decreased production of the antibiotic mupirocin in P. fluorescens 2P24. Furthermore, quantitative proteomic analysis revealed that the PcoR/PcoI quorum-sensing system regulates a diverse range of physiological processes, including mupirocin production and denitrification. Collectively, these findings demonstrate a quorum-quenching role of flavonoids in a PGPR strain, establishing that flavonoids can disrupt quorum-sensing by enhancing the efflux of quorum-sensing signaling molecules. These findings have practical implications for the development of sustainable biocontrol strategies, where leveraging natural plant-microbe interactions could enhance the suppression of plant pathogens without the use of synthetic chemicals.IMPORTANCEFlavonoids are key mediators of plant-microbe interactions; however, their role in regulating microbial signaling remains poorly understood. This study identifies AefR as a flavonoid-sensing regulator in Pseudomonas fluorescens 2P24, revealing a novel quorum-quenching mechanism where flavonoids enhance the efflux of quorum-sensing signals. These findings shed light on the molecular basis of flavonoid-mediated microbial regulation and offer new strategies for sustainable plant health management.